Designing and Explaining the Competency Model in Organizational Interpersonal Communication - Hossein Damghanian; Abbasali Rastegar; Mohammad Yazdani Ziarat (مطالعات مدیریت بهبود و تحول, 2018)
The purpose of this study is to examine the interpersonal communication competencies (ICC) in the organization and identification of its components as well as determine the quality of interaction between them.This research is an applied and developmental as well as analitical and quantitative and the use of interpretive structural modeling method. The statistical population of the research in the analytical section is a group of academic experts and in the quantitative section is all personals of North Khorasan Governmental Executive Agencies; that 17 peoples of experts by using snowball sampling and 373 peoples of personals by using Stratified random sampling were selected as statistical sample. The data collection tools in the analytical section were a researcher made matrix table and in the quantitative section were standard questionnaires that were distributed among the statistical sample after determining their validity and reliability. The results in the analytical section showed important components of  ICC were Empathy, Altercentrism, Self disclosure, Conflict Management, Interaction management, Supportiveness, Flexibility, assertiveness, Social Relaxation, Expressiveness, Immediacy, influencing others and goal orientation that at five different levels of interaction have a positive and significant relationship with together. This Results can help managers and employees to Identifying and strengthening their ICC for achieve effective organizational communications.